Quem@PUC - A tool to find researchers at PUC-Rio - Salgueiro, Mariana D. A.; dos Santos, Veronica; Rêgo, André L. C.; Guimarães, Daniel S.; Haeusler, Edward H.; dos Santos, Jefferson B.; Villas, Marcos V.; Lifschitz, Sérgio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2021)
Quem@PUC is an Information Retrieval System available on the Web that allows searching for researchers and professors based on a keyword list of research related terms. It publicizes research and teaching activities from the PUC-Rio community to society in general. The idea is to integrate information from professors from administrative systems, courses offered, and researchers’ Lattes CVs. Data sources are converted to RDF format using domain ontologies, then stored in a NoSQL database that supports native free-text indexing on triple objects. Search results include names, academic papers, teaching activities, and contact links.